International business and sustainable development goals - Tulder, Rob van; Giuliani, Elisa; Álvarez, Isabel (Progress in international business research, 2023)
The Sustainable Development Goals (SDGs) represent the leading governance frame with which the international community tries to address complex interconnected global issues. The SDGs were adopted in 2015 by all 193 UN member states and were also quickly embraced by most Multinational Enterprises (MNEs), International NGOs and leading business schools. But progress has proved slow. In 2020, the United Nations announced a decade of action to speed-up progress in the area. To what extent and under what circumstances can MNEs help in this effort: revitalize the SDGs and rescue the beneficial effects of globalization? Volume 17 in the series Progress in International Business Research argues that the SDGs can be considered the only relevant agenda for progress in the years to come. This makes it all the more important to critically consider the role played by MNEs, as well as explore the way IB scholarship can help MNEs to walk the talk on the complex issues that affect the sustainable development - thereby leveraging the future shape of globalization. The book contains contributions by established as well as young scholars and is intended to stimulate present and future research, create new forms of conceptualizations and provide first evidence of more focused empirical research on the topic of MNEs and the SDGs.